On Rubus ulmifolius (Rosaceae) and related taxa - Ferrer-Gallego, P. Pablo; van De Beek, Abraham (Phytotaxa, 2021)
Nomenclature issues in the genus Rubus are discussed. In particular, R. ulmifolius and six related names, R. creticus, R. sanctus, R. parviflorus, R. vulgaris, R. non-spinosus, and R. inermis, are discussed. Further support is provided for the suggestions that these seven names are used for only one species. The names R. creticus, R. sanctus and R. parviflorus are homotypic, being R. sanctus and R. parviflorus illegitimate. A lectotype is designated for R. non-spinosus from an image of Barrelier. An epitype is selected for R. vulgaris from a modern specimen collected in Italy and preserved at L.